Novel umami peptides from tilapia lower jaw and molecular docking to the taste receptor T1R1/T1R3 - Shiyan, Ruan; Liping, Sun; Xiaodong, Sun; Jinlun, He; Yongliang, Zhuang (Food chemistry, 2021)
•Umami peptides were the first identified from tilapia lower jaw.•STELFK, VADLMR, DALKKK, FVGLQER and VVLNPVARVE displayed umami taste characteristics.•Asp219, Glu217, and Glu148 in T1R1/T1R3 receptor play critical roles.•Hydrogen bonding and hydrophobic interaction were the important interaction forces. This study aimed to isolate and identify peptides with intense umami taste from tilapia lower jaw. The aqueous extract was separated using ultrafiltration and Sephadex G-15 gel filtration chromatography. The peptide fraction with an intense umami taste was selected by sensory evaluation. The five novel peptides with strong umami taste were VADLMR, STELFK, FVGLQER, DALKKK, and VVLNPVARVE. Electronic tongue analysis and sensory evaluation showed that five peptides had obvious umami taste characteristics, and the recognition thresholds of umami peptides were in the range 0.125–0.250 mg/mL. Molecular docking was used to study the interaction of the peptides and umami taste receptor T1R1/T1R3. The five peptides could perfectly be inserted into the binding pocket of the Venus flytrap domain in the T1R3 subunit. Hydrogen bonding and hydrophobic interaction were the important interaction forces. The five peptides may bind with Asp219, Glu217, and Glu148 in T1R1/T1R3 receptor and produce the umami taste.